Multiple spontaneous jejunal and ileal perforations: a diagnostic challenge - Sunder, Vijayalakshmi; Swaminathan, Shanthi Ponandal; Kawarat, Vikas; Maiyazhagan, Kamalraj; Khanna, Shriram; Mani, Rajeswari; Ross, Kannan (International Surgery Journal, 2021)
Spontaneous multiple jejunal perforations are rare. In India, the commonest cause of small bowel perforation is typhoid fever followed by tuberculosis. We report a case of multiple jejunal and ileal perforations in a 23-year-old young woman who was known to have ulcerative colitis on medical therapy including steroids. She was then diagnosed to have active pulmonary tuberculosis and commenced on anti-tuberculosis therapy. She presented with generalised peritonitis and underwent emergency bowel resection with proximal enterostomy and creation of mucous fistula of the distal ileum. Post-operative course was stormy due to sepsis and she eventually succumbed on the 3rd post-operative day. Histopathological examination revealed non-specific changes and was not contributory to diagnosis. Possible causes of spontaneous jejunal perforations are discussed and the literature is reviewed. This case, despite a fatal outcome, is being reported to highlight the need for high index of suspicion in such situations.